Flexible write-once–read-many-times memory device based on a nickel oxide thin film - Yu, Q. (2013)
A write-once-read-many-times (WORM) memory device based on conduction switching of a NiO thin film in a metal-insulator-metal structure is fabricated on a flexible substrate. The device can be switched from a low-conductance state (unprogrammed state) to a high-conductance state (programmed state) with the formation of conductive filament(s) in the NiO layer. The two memory states can be easily distinguished at a very low reading voltage. For example, at the reading voltage of 0.1 V, the current ratio of the state programmed at 3 V for 1 μs to the unprogrammed state is larger than 104. The WORM device exhibits good reading-endurance and data-retention characteristics. The flexible device is promising for low-cost and low-power archival storage applications.